Pendampingan Pelestarian Budaya Upacara Mappalili Melalui Kegiatan Tudang Sipulung Dalam Menunjang Geopark Maros-Pangkep - Al Hazar, Badrizal; Zulfi Al'Ghani, Muhammad; Bohari, Nurul Aulia; Handayani, Fitri (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
Mappalili Ceremony is a sacred tradition of the Bugis-Makassar community that embodies profound ecological, social, and spiritual values in agricultural management. The preservation of this cultural heritage was carried out through the Tudang Sipulung activity as a form of community engagement to support the development of the Maros-Pangkep Geopark. The activity took place at the Balla Kalompoang Traditional House, Labakkang District, Pangkep Regency, involving 35 participants consisting of traditional leaders, local government officials, geopark managers, and community members. The method employed a participatory approach through discussions, the distribution of monograph books, cultural preservation models, and pre-test and post-test evaluations to measure the participants’ understanding of Mappalili’s cultural values. The results indicated a significant improvement in participants’ comprehension, with the high category increasing from 0% to 71.43% after mentoring activities. Tudang Sipulung proved to be an effective medium for cultural communication and education, strengthening collective awareness in preserving local traditions and supporting the geopark as an integrated space between natural conservation and cultural heritage. This study recommends the involvement of younger generations and local government support to ensure the sustainability of the Mappalili Ceremony as a cultural legacy that contributes to the development of tourism based on local wisdom.